Graph coloring for determining courier frequency - Setiawan, Tabah Heri; Beltsazar, Ferdinand; Aden, Aden; Gunawan, Gani; Zarista, Ramzil Huda (Universitas Islam Negeri Raden Intan Lampung, 2023)
The exponential growth of online transactions in Indonesia has intensified the competition among courier service providers to ensure efficient goods delivery, prompting the need for exceptional performance. However, this surge has also brought forth various challenges, including imbalanced courier allocation, intricate delivery routes, and sprawling coverage areas, resulting in delays and extended working hours for couriers. This research, conducted in Jakarta, centers on a logistics and courier service company grappling with a critical courier shortage, leading to overburdened personnel and extended work hours. To address this issue, we employed graph coloring, rooted in graph theory, as a novel approach to determine the ideal number of couriers based on the route and delivery area. Through graph coloring, delivery routes, and areas can be optimized so that each courier has the same average route length and area and does not exceed the threshold limit set by the company. The number of delivery routes and areas generated from graph coloring shows the number of couriers required for the company. The results of this research obtained 27 routes that show the need for the ideal courier frequency so that the delivery of goods can be on time without extending the courier's working hours.